Canine thoracolumbar intervertebral disk herniation and rehabilitation therapy after surgical decompression: A retrospective study - Jeong, In Seong; Piao, Zhenglin; Rahman, Md Mahbubur; Kim, Sehoon; Kim, Nam Soo (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The purpose of this study was to evaluate the clinical outcome of surgical decompression and rehabilitation therapy in dogs with thoracolumbar intervertebral disk herniation (IVDH). Materials and Methods: After surgery, physiotherapeutic rehabilitation was performed by a combination of electrotherapy, infrared therapy, training for standing, deep tendon reflex, and aquatic treadmill exercise. A total of 186 dogs were selected from the hospital records and included in two groups: the rehabilitated group (RG, n = 96) and non-rehabilitated group (NRG, n = 90). Dogs in each group were subdivided into three groups based on a pre-operative clinical severity grading system and those in grades 2–4 were included in this study. Post-operative neurologic functions, unassisted standing, walking, and the success rate of both groups were evaluated and compared Results: Overall, 86.46% (83/96) of dogs had a successful neurologic outcome in the RG group, which was significantly (p < 0.01) higher than the NRG group 52.22% (47/90). Interestingly, the success rate differed when the preoperative grading system was considered. The success rates of grades 2, 3, and 4 were 97.14% (34/35), 97.33% (42/45), and 43.75% (7/16), respectively, in the rehabilitated groups, whereas in the non-rehabilitated groups, success rates were 82.35% (28/34), 51.85% (14/27), and 17.24% (5/29), respectively. The differences in success rates among the groups according to grading were 14.79%, 41.48%, and 26.51%, respectively, indicating that the proposed rehabilitation therapy is remarkably advantageous for increasing the success rate. Conclusion: Rehabilitation therapy after surgical decompression of thoracolumbar IVDH improves neurologic functions and increases the success rate, especially when the preoperative pathological condition is severe. J. Adv. Vet. Anim. Res., 6(3): 394-402, September 2019